Aspergillus collected in specific indoor settings: their molecular identification and susceptibility pattern - Simões, Daniela (2020)
Exposure to Aspergillus conidia is an increased risk factor for the development of respiratory symptoms. The emergence of azole resistance in Aspergillus fumigatus is a major concern for the scientific community. The aim of this study was to perform the molecular identification of Aspergillus species collected from different occupational and non-occupational indoor settings and to study the azole susceptibility profile of the collected Fumigati isolates. The selected Aspergillus isolates were identified as belonging to the sections Fumigati, Nigri Versicolores, Terrei, Clavati and Nidulantes. All the Aspergillus fumigatus were screened for azole resistance using an agar media supplemented with itraconazole, voriconazole and posaconazole. None of the tested isolates showed resistance to those azoles. Knowledge of Aspergillus epidemiology in specific indoor environments allows a better risk characterization regarding Aspergillus burden. This study allowed the analysis of the molecular epidemiology and the determination of the susceptibility pattern of Aspergillus section Fumigati found in the studied indoor settings.